2012
DOI: 10.1007/s10577-012-9302-3
|View full text |Cite
|
Sign up to set email alerts
|

Dicentric chromosomes: unique models to study centromere function and inactivation

Abstract: Dicentric chromosomes are products of genome rearrangement that place two centromeres on the same chromosome. Depending on the organism, dicentric stability varies after formation. In humans, dicentrics occur naturally in a substantial portion of the population and usually segregate successfully in mitosis and meiosis. Their stability has been attributed to inactivation of one of the two centromeres, creating a functionally monocentric chromosome that can segregate normally during cell division. The molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 53 publications
2
98
0
1
Order By: Relevance
“…In both patients, there is a pseudodicentric chromosome with inactivation of the Y centromere, resulting in a functionally monocentric chromosome. The literature shows that functionally monocentric chromosomes are usually stable and segregate normally during cell division [Stimpson et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…In both patients, there is a pseudodicentric chromosome with inactivation of the Y centromere, resulting in a functionally monocentric chromosome. The literature shows that functionally monocentric chromosomes are usually stable and segregate normally during cell division [Stimpson et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, dicentric chromosomes are thought to be generated from arm breakage or shortening of telomeres, and consecutive rearrangements (Frias et al 2012). These chromosomes are unstable due to the presence of two active centromeric regions that may attach to opposite spindle poles, resulting in chromosome bridges and breakage in anaphase (Stimpson et al 2012). In rare instances, dicentric chromosomes can stabilize due to the inactivation of one of the two centromeres by deletion or by epigenetic silencing (Earnshaw and Migeon 1985;Merry et al 1985;Earnshaw and Cooke 1989;Stimpson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Most of our current understanding of how dicentrics are stabilized comes from studies of artificially-induced or engineered dicentric chromosomes in yeast (Pobiega and Marcand 2010; Sato et al 2012), fruit flies (Agudo et al 2000), and human cell lines (Higgins et al 1999; Higgins et al 2005; Stimpson et al 2010; Stimpson et al 2012), as well as a few examples of dicentric chromosomes in found in plants (Sears and CĂąmara 1952; Han et al 2006; Zhang et al 2010; Gao et al 2011; Koo et al 2011; Liu et al 2015) and human patients (Therman et al 1989; Maraschio et al 1990; Fisher et al 1997; Page and Schaffer 1998; Sullivan and Willard 1998; Lange et al 2009; Stimpson et al 2012). In some engineered systems, the dicentric chromosome can simply break in order to re-establish monocentric chromosomes (Pobiega and Marcand 2010; Sato et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In other engineered or patient-derived dicentrics, chromosome fusions can be stably inherited because the two centromeres on a fusion chromosome are close enough to each other to act as a single centromere (Koshland et al 1987; Page and Shaffer 1998; Sullivan and Willard 1998; Higgins et al 1999; Lange et al 2009). However, distance between the centromeres does not fully explain the stable maintenance of dicentric chromosomes, and in many cases, there is inactivation of one of the centromeres to re-establish functionally monocentric chromosomes (Stimpson et al 2012). Centromere inactivation can either occur by genetic or epigenetic inactivation of one centromere.…”
Section: Introductionmentioning
confidence: 99%